Complications of standard versus long cephalomedullary nails in the treatment of unstable extracapsular proximal femoral fractures: A randomized controlled trial. Issue 2 (February 2023) - Martí-Garín, David; Fillat-Gomà, Ferran; Marcano-Fernández, Francesc Antoni; Balaguer-Castro, Mariano; Murias Álvarez, Juan; Pellejero, Raul; Sánchez Fernández, Joël; Torner, Pere; Muñoz Vives, Josep Maria
Abstract: Aims: To compare in a prospective randomized trial the mechanical complications in patients with unstable extracapsular proximal femur fractures without subtrochanteric extension (AO/OTA 31-A2 and 31-A3) Methods: We prospectively studied 182 patients with unstable extracapsular proximal femur fractures without fractures lines extending more than 3 cm below the lesser trochanter, randomized to receive either a 'standard' (240 mm) nail or a long nail and followed them up for 1 year. Results: We found no difference in the incidence of mechanical or general complications between the two groups, no cut-outs, no fractures of the tip the implant, 1 cut-through and 2 malrotations in the LN group, 2 non-unions that were reoperated, one on each group. The commonest complication was blade lateral migration, 13 (14%) patients in SN and 6 (9%) in the LN. The operating time was shorter in the SN group 51 minutes compared to 67 minutes in the LN group (p=0.000075). The mortality at 1, 3 and 12 months in the SN group was of 2%, 6%, 12% while in the LN group was 12%, 18% and 22%. These differences where significative at 1 (p=0.007) and 3 months (p=0.013), but not at 12 months (p=0.075). Conclusions: We recommend the use of standard nails (240 mm) for this group of fractures, since it does not produce more mechanical complications, and it is faster, cheaper and easier to interlock distally.